Influencing Factors of EV Ride-Hailing Adoption in Jakarta: A Case Study of GoRide Electric - A Audli Natakusuma; Putro, Utomo Sarjono (Journal Integration of Management Studies, 2025)
The electrification of urban transport is critical to achieving global emissions reduction targets, particularly in emerging economies where motorcycle-dominated traffic significantly contributes to air pollution. Road transport accounts for nearly 46% of the city’s total emissions in Jakarta, with motorcycles representing over 80% of private vehicles. As Indonesia’s leading ride-hailing platform, Gojek launched GoRide Electric as part of its GoTo Net Zero Emission 2030 commitment. However, consumer adoption of this electric alternative remains limited, underscoring a gap between supply-side readiness and demand-side behavior. This study aims to identify and evaluate key consumer-level factors that influence the adoption of GoRide Electric in Jakarta. Using a mixed-method design, a literature synthesis of five peer-reviewed EV ride-hailing adoption studies was conducted to extract 15 sub-variables, which were consolidated into four theoretical constructs: Affordability, Reliability, Environmental Benefit, and Social Influence. These constructs were operationalized into a 15-item questionnaire and validated through a 4-point Likert-scale survey of 141 active Gojek users. The data underwent descriptive quantitative analysis using SPSS to rank variable importance. Results indicate that Environmental Benefit is the most influential factor (M = 3.39), followed by  Reliability as the second most influential factor (M = 3.35). Affordability ranked third (M = 3.15), while Social Influence scored the lowest (M = 2.78), indicating weak peer-driven motivation. This study contributes to the literature on sustainable mobility by contextualizing EV adoption behavior in a Southeast Asian megacity and provides actionable insights for policymakers and platform operators to design consumer-centric interventions for EV ride-hailing uptake.